Immune Checkpoint Inhibition for Pancreatic Ductal Adenocarcinoma: Current Limitations and Future Options - Kabacaoglu, Derya; Ciecielski, Katrin J.; Ruess, Dietrich A.; Algül, Hana (Frontiers in Immunology, 2018)
Pancreatic ductal adenocarcinoma (PDAC), as the most frequent form of pancreatic malignancies, still has a dismal prognosis. Due to its late detection most patients are ineligible for surgery, and chemotherapeutic options are limited. Tumor heterogeneity and a characteristic structure with crosstalk between the cancer/malignant cells and an abundant tumor microenvironment make PDAC a very challenging puzzle to solve. So far, targeted therapies have failed to substantially improve the overall survival of PDAC patients. Immune checkpoint inhibition, as an emerging therapeutic option in cancer treatment shows promising results in different solid tumor types and hematological malignancies. However, PDAC doesn’t respond efficiently to immune checkpoint inhibitors anti PD-1 or anti CTLA-4 alone or in combination. PDAC with its immune-privileged nature, starting from the early pre-neoplastic state, seems to escape from the anti-tumor immune response unlike other entities. Different mechanisms are postulated how cancer cells achieve immune-privileged status. Among them are decreased antigenicity and impaired immunogenicity via both cancer cell intrinsic mechanisms and an augmented immunosuppressive tumor microenvironment. Here we seek to shed light on the recent advances in both bench and bedside investigation of immunotherapeutic options for PDAC. Besides, we aim to compile recent data about how PDAC adopts immune escape mechanisms, and how these mechanisms might be exploited therapeutically in combination with immune checkpoint inhibitors such as PD-1 or CTLA-4 antibodies.